PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BAGIAN SALES PT NASMOCO CABANG MAGELANG - Nurina Szafira Putri; Agus Hermani DS (Jurnal Ilmu Administrasi Bisnis, 2018)
PT. Nasmoco Magelang Branch Office as a company in automotive field still have some low performance employees such as the achievement of targets that is not maximal either quantity and quality, lack of controlling from supervisor and lack of motivation from the employees. It is predicted because there is leadership and employee work motivation issue in the corporate. This research aim is to determine how the influence given by leadership and work motivation on the performance of employees of PT. Nasmoco Magelang Branch Office. The type of this research is explanatory type (explanatory research), with 50 respondents involved. Data collection using questionnaire with Likert measurement scale. Using validity and reliability test as data analysis method, also correlation coefficient (R), regression test, coefficient of determination (R2), and significance of t test and F test with SPSS 16.0 application. The results of this research indicate that leadership and work motivation variables have a significant, strong and positive influence to employee performance. Two variables have been tested separately or simultaneously show the result that leadership variables significantly have a strong positive effect on employee performance variable. That means if leadership and work motivation are good then the employee performance will be high, otherwise if leadership and work motivation are not good then the employee performance will be low. From coefficient of determination result, the amount of donations owned by leadership variables is bigger than the amount of donation owned by the variable of work motivation. Suggestions that can be submitted are the company must improve leadership and work motivation to have high employee performance, such as a clear direction from supervisor, supervisor should be able to motivate employee to achieve the target work, and supervisor can improve their control to the performance of their employee. Also by provide rewards for employee that work great so the employee will work with more enthusiast and will continously fix their performance so that their job will be better.